1964
DOI: 10.1172/jci104941
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Ventilation-Perfusion Relationships in the Lung after Breathing Inert Dust or Bronchoconstrictor Aerosols and after Short Periods of Voluntary Hyperventilation

Abstract: The increase in airway resistance that follows the breathing of fine inert dust was first demonstrated by DuBois and Dautrebande (1), who also showed that an aerosol of carbachol had the same effect. The compliance of the lungs was reduced, which led these authors to conclude that the increased airway resistance was unevenly distributed. Constantine and associates (2) confirmed the increased airway resistance in similar experiments and also noted an increase in intrathoracic gas volume, which they attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1967
1967
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous studies (Raine and Bishop, 1964;Norris and Bishop, 1966) showed an increase in the slope of the nitrogen plateau after carbachol and calcium carbonate dust in normal subjects, 'reactors', and patients with chronic bronchitis and bronchial asthma. However, only the mean value of the N2 gradient was reported.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies (Raine and Bishop, 1964;Norris and Bishop, 1966) showed an increase in the slope of the nitrogen plateau after carbachol and calcium carbonate dust in normal subjects, 'reactors', and patients with chronic bronchitis and bronchial asthma. However, only the mean value of the N2 gradient was reported.…”
Section: Discussionmentioning
confidence: 88%
“…Following the administration of a variety of bronchoactive agents, changes have been studied in ventilation (Colldahl, Holmgren, Pegelow & Svanborg, 1964;Stanescu, Teculescu, Pacararu & Popa, 1968), mechanical function (McIlroy & Marshall, 1956;Constantine, Dautrebande, Kaltrieder, Lovejoy, Morrow & Perkins, 1959; Dautrebande, Lovejoy & Constantine, 1960;Lovejoy, Constantine, Flatley, Kaltrieder & Dautrebande, 1961 ;Dubois & Dautrebande, 1958;Bouhuys, Hunt, Kim & Zapletal, 1969;Cade, Woolcock, Rebuck & Pain, 1971), ventilationblood-flow relationships (Raine & Bishop, 1964;Norris & Bishop, 1966) and gas transfer (Bouhuys, Georg, Jonsson, Lundin & Lindell, 1960;Stanescu & Teculescu, 1969).…”
mentioning
confidence: 99%